DAMPAK BULLYING TERHADAP PERKEMBANGAN PSIKOLOGIS BELAJAR SANTRI TPQ AL – FURQON LAMPEYAN KEDUNGKUMPUL SUKORAME - Ayu Putri, Lidya; Junaidi, Mahbub; Ashrofun Nashr, M. Naqouib (-, 2025)
This research was conducted to determine the beginning of bullying at TPQ Al-Furqon Lampeyan Kedungkumpul Sukorame. The impact of bullying on the psychological development of students’ learning generally occurs in non formal educational institutions or in the community. The impact of bullying on the psychology of students occurs due to their physical condition, social status, family economy and parents’ educational backgrounf. The aim of this research is to find out the causes of bullying at TPQ Al-Furqon and the impact and impact of bullying on the psychological development of students’ learning and how to prevent it. The research results show. The causes of bullying at TPQ Al-Furqon Lampeyan are verbal, including physical condition factors, family background factors, and broken home factors. The impact of bullying on the psychological development of students is that victims of bullying are often gloomy, silent and late when coming to TPQ, students who are victims of bullying tend to be a solitay person and not group with other students. The way to prevent bullying at TPQ is to involve teachers, students, parents and the community so that when it occurs in the TPQ environment it is the teacher’s responsibillitylll